Relationship Between Hemodialysis Duration and Fatigue in Chronic Kidney Disease (CKD) Patients During Hemodialysis - Hasballah Hasballah; Bayhakki Bayhakki; Erika Erika (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Introduction: Chronic Kidney Disease (CKD) is a progressive and irreversible kidney function disorder in which the body fails to maintain metabolism and fluid-electrolyte balance, and causes retention of urine and other nitrogenous wastes in the body. The causes of CKD vary in the form of structural or functional abnormalities with a decrease in the Glomerular Filteration Rate (GFR) of less than 60 ml/minute/1.73. Methods: This study used a correlation descriptive design with a cross sectional approach. The research sample was 59 respondents who were taken using a purposive sampling technique. The Functional Assessment of Chronic Illness Therapy (FACIT) Fatigue Scale is used to measure fatigue. This study was analyzed using the Spearman Rank test. Results: Shows that the majority of CKD patients underwent hemodialysis with a duration of 4 hours (91.5%). The majority of respondents are women (52.5%). The majority of respondents are in the age group of 56-65 years (25.4%). The results of the analysis showed that the majority of respondents experienced mild fatigue (45.8%) with a p value = 0.936 0.154. Conclusion: There is no relationship between the duration of hemodialysis and the fatigue of Chronic Kidney Disease (CKD) patients while undergoing hemodialysis at Arifin Achmad Hospital.